A critical review of social resilience assessment frameworks in disaster management - Saja, A.M. Aslam; Goonetilleke, Ashantha; Teo, Melissa; Ziyath, Abdul M. (International journal of disaster risk reduction, 2019)
The role of social resilience in disaster management continues to gain increasing attention and interest from both researchers and practitioners. This paper critically reviews existing frameworks and methods to understand their application in a disaster context, to highlight key challenges and future directions for developing robust social resilience assessment frameworks. The analysis revealed a lack of consistency in key concepts used to measure social resilience to disasters. This results in significant confusion in the way key concepts are understood, interpreted, and applied. Due to the multi-faceted nature of social resilience concepts, there are pronounced theoretical and practical difficulties in carrying out a rapid, but rational, accurate, and meaningful assessment of social resilience to disasters. Many of the key process-oriented indicators are not included in the existent social resilience frameworks, since they are not easy to operationalise due to their dynamic nature. Therefore, a comprehensive social resilience framework that can be adapted to different contexts and integrated with specific measurement tools and guidelines is necessary. Such a comprehensive framework can make resilience measurement consistent across geographies by adapting it with context specific resilience characteristics.